PEMBELAJARAN SENTRA IMTAQ BERBASIS MEDIA AUDIOVISUAL PADA MASA PADEMI DALAM MENGEMBANGKAN KEMAMPUAN KOGNITIF ANAK - Herni Sri Rahayu (Abata : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
Audiovisual media is one way to keep learning activities going during the current pandemic. We know that currently not only Indonesia but even the whole world is being affected by the corona virus (covid-19), therefore the government recommends that the process of learning activities be carried out online or distance learning to make it easier for teachers to continue to provide learning to children so that learning objectives can be achieved. still well conveyed, the purpose of conducting imtaq center learning activities based on audiovisual media during the pandemic is to develop the cognitive abilities of children aged 4-5 years at TKIT Insan Cendekia Mathla'ul Anwar to find out (1) what preparations are made by teachers in learning centers audiovisual media-based imtaq during the pandemic in developing cognitive abilities of children aged 4-5 years?, (2) How is the audiovisual media-based imtaq learning center during the pandemic in developing cognitive abilities of children aged 4-5 years?, (3) What are the characteristics of development cognitive of children aged 4-5 years?, (4) What are the supporting and inhibiting factors experienced by teachers in learning audiovisual media-based Imtaq centers during the pandemic in developing the cognitive development of children aged 4-5 years at TKIT Insan Cendekia Mathla;ul Anwar?. This study uses a qualitative approach with a qualitative descriptive method. The results of research conducted by researchers show that learning at the IMTAQ center using audiovisual media is considered very efficient in the midst of a pandemic like today in addition to minimizing the spread of Covid-19 and so that learning objectives can still be carried out properly